Metabolites in heart tissue measured during heat ramp exposure experiments on the cellular metabolism of the European oyster, Ostrea edulis - Reddin, Carl; Götze, Sandra; Ketelsen, Isabel; Busack, Michael; Lannig, Gisela; Bock, Christian; Pörtner, Hans-Otto (PANGAEA, 2025)
This dataset contains heart tissue metabolite data measured during heat ramp experiments of the European oyster, Ostrea edulis. We studied organismal and heart tissue cellular responses of the European oyster, Ostrea edulis, challenged by rapid warming (+2°C/h) and gradual warming (+2°C/24h). Specimens were collected as wild adults from the estuary of the Ría de Ferrol (Spain, 43°27.64'N and 8°12.04'W) in October 2020 and March 2021. Specimens were sampled at each temperature and dissected on ice. One dimensional 1H-NMR spectroscopy was carried out on heart tissue in an ultra-shielded vertical 9.4 T NMR spectrometer (Advance III HD 400 WB, Bruker-BioSpin GmbH, Germany) equipped with a triple tuned 1H-13C-15N-probe for 1.7 mm NMR tubes. See manuscript for further methodological details and results interpretation.
Keywords: Bivalve; Europe; European flat oyster; heart; Laboratory experiment; metabolomics; Ocean climate change; temperature ramp